Parliamentary committee systems : conference report, Dhaka, 27-28 May 1999. (Bangladesh Jatiya Sangsad, Institute of Parliamentary Studies, 1999)
Contributed articles presented at the Conference on Comparative Constitutional Law: Parliamentary Committee Systems.